An Overview of the Potential Impacts of Climate Change on Groundwater Resources (Journal of Informatics and Mathematical Sciences, 2017)
Climate change has been consistently observed over the past decades to be associated with changes and/or modifications of components of the hydrological systems. Observational records and global and regional climate projections indicate that both surface-water and groundwater resources are vulnerable to climate change and variability. Thus, understanding the impacts of climate change and variability on groundwater systems is integral to better planning and efficient management of groundwater resources. However, assessing and predicting the effects of climate change on groundwater systems is relatively difficult due to the uncertainties associated with the spatial and temporal prediction of future climates. This review provides an overview of the key components of groundwater hydrology in relation to climate change. The effects of changes in climate on groundwater in soil, deep vadose and saturated zones are assessed. The responses of groundwater recharge, discharge, quality and changes in storage to climate change are assessed on inter-annual to multi-decadal or longer geologic time scales.
Keywords: Climate change; Global and regional; Hydrological systems; Groundwater resources; Potential impacts